SPECTRUM AND CLINICAL PROFILE OF NON-VENEREAL GENITAL DERMATOSES IN ADULT MALES: A PROSPECTIVE OBSERVATIONAL STUDY - Dr Mohit Saini , Dr Rajendra Devanda , Dr Khushboo Gupta , Dr Mukesh Kumar Saini , Dr U.S Agarwal (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Non-venereal genital dermatoses (NVGD) encompass a diverse group of dermatological conditions affecting the male genitalia, often mimicking sexually transmitted infections (STIs). Misdiagnosis can lead to psychological distress, social stigma, and inappropriate treatment